Strategi Peningkatan Aktivitas Jasmani Siswa Sekolah Dasar di Luar Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan di Indonesia - Widodo -- (Jurnal Pendidikan dan Kebudayaan, 2014)
This article aims to explain and provide ideas dan suggestion on strategic in physical activity promotion of primary school students beyond physical education classroom. The programs should be developed in a pattern of development that is integral to the educational involving the three parties i.e. schools, parents, and community, as well as government support. Teacher level of strategies: 1 ) socialization by the school principal , 2) the integration of health knowledge to other subjects ; 3 ) the development of incentive programs ; 4 ) rearrangement of homework; and 5) expanding partnerships. The school level strategies: 1) improvement of school management; 2) preparation of daily physical activity program; 3 ) the arrangement of space and equipment; and 4) Parents Forum. The implementation need to combine efforts with the school teachers and families in a professional manner so that students actively engaged at least 90 minutes per day, i.e. 30 minutes in school and 60 minutes in the home or community. Forms of activity that can be applied: 1) getting students to and from school by involving volunteers from the parents/seniors; 2) applying the Walking School Bus models, and 3) active transportation programs. ABSTRAK Artikel ini bertujuan untuk mengkaji aktivitas jasmani dan memberikan sumbangan pemikiran tentang upaya strategis peningkatan aktivitas jasmani siswa sekolah dasar di luar jam pembelajaran pendidikan jasmani, olahraga, dan kesehatan. Program peningkatan hendaknya dikembangkan dalam sebuah pola pembinaan yang integral dari upaya pendidikan dengan melibatkan tiga pihak, yaitu sekolah, orangtua, dan masyarakat, serta dukungan pemerintah. Strategi pada tingkatan guru: 1) sosialisasi oleh kepala sekolah; 2) integrasi pengetahuan kesehatan ke mata pelajaran lainnya; 3) pengembangan program insentif; 4) meramu ulang pekerjaan rumah (PR); dan 5) memperluas kemitraan. Strategi pada tingkat sekolah: 1) perbaikan manajemen sekolah; 2) penyusunan program aktivitas jasmani harian; 3) penataan ruang dan perlengkapan; dan 4) forum orang tua. Pelaksanaannya perlu menggabungkan upaya guru dengan sekolah dan keluarga secara profesional agar siswa aktif bergerak setidaknya 90 menit per hari; yaitu 30 menit di sekolah dan 60 menit di rumah atau masyarakat. Bentuk kegiatan yang dapat diterapkan: 1) mengajak siswa pergi dan pulang sekolah dengan melibatkan relawan dari orang tua/senior; 2) menerapkan model Bus Sekolah Berjalan; dan 3) program transportasi aktif.